Evaluation of Antibiotic Use in Pneumonia Patients with Gyssens Method - Wijaya, Dhani; Alifah, Nabilah Nur; Rahmadanita, Fathia Faza; Indrawijaya, Yen Yen Ari; Susantin, Anggita Meila (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2025)
Pneumonia has become a disease that threatens human health and life. A bacterial infection can cause pneumonia, making antibiotics the appropriate choice of therapy. Antibiotics must be used appropriately to avoid the development of resistance. This study qualitatively evaluates the use of antibiotics in pneumonia patients. This cross-sectional observational study utilised the medical records of patients from Dumai City General Hospital retrospectively. Evaluation of the use of antibiotics qualitatively using the Gyssens flow chart. All medical record data of pneumonia patients hospitalised in January–December 2021 became the study population. The inclusion criteria were complete medical records of pneumonia patients aged 18-72 years who received antibiotic prescriptions. Patients who died were excluded from the study. This study involved 57 samples that met the inclusion criteria. Qualitatively, antibiotic use fell into the following categories: Category 0 (82.4%), Category II (10.5%), Category III (1.8%), Category IV C (3.5%), and Category IV A (1.8%).